Heart-specific Rpd3 downregulation enhances cardiac function and longevity. - Kopp, Z.A.; Hsieh, J.L.; Li, A.; Wang, W.; Bhatt, D.T.; Lee, A.; Kim, S.Y.; Fan, D.; Shah, V.; Siddiqui, E.; Ragam, R.; Park, K.; et al. (Aging, 2015)
Downregulation of Rpd3, a homologue of mammalian Histone Deacetylase 1 (HDAC1), extends lifespan in Drosophila melanogaster. Once revealed that long-lived fruit flies exhibit limited cardiac decline, we investigated whether Rpd3 downregulation would improve stress resistance and/or lifespan when targeted in the heart. Contested against three different stressors (oxidation, starvation and heat), heart-specific Rpd3 downregulation significantly enhanced stress resistance in flies. However, these higher levels of resistance were not observed when Rpd3 downregulation was targeted in other tissues or when other long-lived flies were tested in the heart-specific manner. Interestingly, the expressions of anti-aging genes such as sod2, foxo and Thor, were systemically increased as a consequence of heart-specific Rpd3 downregulation. Showing higher resistance to oxidative stress, the heart-specific Rpd3 downregulation concurrently exhibited improved cardiac functions, demonstrating an increased heart rate, decreased heart failure and accelerated heart recovery. Conversely, Rpd3 upregulation in cardiac tissue reduced systemic resistance against heat stress with decreased heart function, also specifying phosphorylated Rpd3 levels as a significant modulator. Continual downregulation of Rpd3 throughout aging increased lifespan, implicating that Rpd3 deacetylase in the heart plays a significant role in cardiac function and longevity to systemically modulate the fly's response to the environment.